Evaluation of the Tofu Craftsman Small and Medium Industry Development Program in Serang City, Banten 2020 - Leo Agustino; Cynthia Utami Damayanti; Jonah Silas; Mohammad Agus Yusoff (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
This research focuses on the tofu industry sector development program in Lopang Village. One of the problems studied in this study is that the DinkopUKMPerindag of Serang City does not provide information to tofu craftsmen about the training that will be held. This research aims to evaluate the Small and Medium Industry Development Program (Case Study of Tofu Craftsmen in Lopang Village) using the CIPP theory by Daniel Stufflebeam. This research uses descriptive qualitative methods by analyzing the results of interviews, observations, interviews, documentation and document studies. The results of this study indicate that the SMI development program case study of Tofu Craftsmen in Lopang Village has not fully run well. The evaluation includes i) context, the program does not solve the problem according to the needs of tofu craftsmen; ii) input, mentoring activities are still carried out accidentally; iii) process, there are still some obstacles, iv) product, it has not achieved the program objectives of improving the quality and quantity of tofu products.